A decrease in cardiovascular risk factors in healthy 40-year-old Swedish men between 1980-1983 and 1991-1992. - Tornvall, P; Båvenholm, P; Hellénius, M; Karpe, F; Regnström, J; de Faire, U (1996)
BACKGROUND: Cardiovascular risk factors were compared between two samples of urban middle-aged healthy men investigated in 1980-1983 (n = 106) and 1991-1992 (n = 118), respectively. METHODS: All subjects, who served as controls in an ongoing study on mechanisms behind myocardial infarction, were randomly selected from a register that contains all the inhabitants (1.65 million) in the Stockholm Metropolitan Area. The study programme included recordings of weight, height, smoking habits, blood pressure and blood sampling. Blood and lipoprotein lipid levels, glucose concentrations before and during an oral glucose tolerance test and fibrinogen levels were determined. RESULTS: The 1991-1992 sample had lower systolic blood pressure and lower concentrations of total blood cholesterol, fasting blood glucose and fibrinogen than the 1980-1983 sample. The lower total blood cholesterol level in the 1991-1992 sample was due to a decrease in low- and high-density lipoprotein cholesterol concentrations. In addition, a tendency was seen towards a decrease in prevalence of smoking in the latter sample. No differences were noted in body mass index, diastolic blood pressure, oral glucose tolerance or total triglycerides between the two samples.